Predicted molecules followed by experimental validation for protecting human neurons from oxidative stress–induced cytotoxicity - Xuyu Yang; Joo-Youn Lee; Farbod Moghadam; Joseph Steiner; Soo-Kyung Kim; Neha Ganjur; Adrian J. de Almenara; Brian M. Stoltz; Y. Peng Loh; William A. Goddard (Proceedings of the National Academy of Sciences, 2025)
Alzheimer neurodegenerative disease (AD) has had a major impact worldwide, with no effective drugs for treatment. We discovered and reported earlier that neurotrophic factor-α1 (NF-α1)/carboxypeptidase E (CPE) reversed neurodegeneration and cognitive dysfunction in AD mouse models. We then predicted computationally and validated experimentally that CPE interacts with a pharmacophore of six residues on the 5-HT1E receptor (HTR1E) to activate the ERK-BCL2 signaling pathway leading to protection of human neurons against oxidative stress–induced cell death. We now report using this pharmacophore for in silico virtual screening of ~6 million small molecules to discover candidates with similar binding and neuroprotective properties as CPE. This in silico search identified a molecule (Z124) that was verified experimentally to bind to HTR1E with protective efficacy comparable to NF-α1/CPE but requiring a higher concentration. Next, we carried out R-group design optimization based on Z124 to identify 4 compounds predicted to have much better efficacy than Z124. These compounds were synthesized and tested for neuroprotective activity. All four compounds showed binding to HTLA-HTR1E cells comparable to CPE. We determined the Kd for two of these compounds: R9, 1.38 ± 0.2 nM, and R10, 2.1 ± 0.2 nM, to be over 15 times better than CPE. Furthermore, all four new compounds showed protective activity against oxidative stress–induced cytotoxicity in human HEK293 cells stably transfected with HTR1E, as well as human primary neurons. Mechanistically, R9 and R10 activated ERK phosphorylation and increased the mitochondria prosurvival protein, BCL2, making them excellent candidates for further development as a drug to treat neurodegenerative diseases.